Penerapan Metode Pembelajaran Kreatif-Produktif untuk Meningkatkan Hasil Belajar Peserta Didik - Marzuki Marzuki; Sadrina Sadrina; Helmawati Helmawati (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
Learning faced problems such as less participated from students, minor activities which affect no creative productions. To effort these problems, teachers are expected to choose the right learning method, which aim to create active students, creative, and innovative in learning. Productive-creative learning model is perceived as one of best models which students-centered learning approach. However, this study aims to determine the study result after the implementation of productive creative learning methods in the lighting installation engineering subjects in class XII of SMKN 2 Banda Aceh. In addition, another objective is to describe the response of students for creative-productive learning methods. This study used a quantitative study with a quasi-experimental method and involved 19 students as samples. Data was collected through tests form and questionnaires. The results showed that the application of creative-productive learning methods in lighting installation engineering subjects could improve learning outcomes as evidenced by the average posttest score achieved by the control group significantly less than the experimental group. Supported by the results of responses, it showed a positive response with categorization of good. It could conclude that the application of creative-productive learning methods has an important influence on the achievement of student learning outcomes in class XII TITL SMKN 2 Banda Aceh.